Discrimination of Virgin and Recycled Polyethylene Based on Volatile Organic Compounds Using a Headspace GC-MS Coupled with Chemometrics Approach. (December 2020) - Chen, Zhi-Feng; Lin, Qin-Bao; Song, Xue-Chao; Chen, Sheng; Zhong, Huai-Ning; Nerin, Cristina
Highlights: Volatile organic compounds (VOCs) markers were found betweenrecycled and virgin polyethylene (PE). Based on function and sources, VOCsin recycled and virginPE were classified into aliphatic hydrocarbons, additives, contaminants and miscellaneous. A method of chemometricscombinedwith headspace gas chromatography coupled to mass spectrometry (HS-GC-MS)was successfully used to discriminate recycled PE. Abstract: A method of headspace gas chromatography coupled to mass spectrometry (HS-GC-MS) followed by multivariate statistical analysis was applied to identify recycled and virgin polyethylene (PE). Under the optimized conditions, a total of 47 volatile organic compounds (VOCs) were detected, which can be categorized as aliphatic hydrocarbons, additives, contaminants and miscellaneous. Among them, 16 volatile markers for discrimination between virgin and recycled PE were selected based on orthogonal partial least squares discriminant analysis (OPLS-DA) and non-parametric test. Most of these compounds were aliphatic hydrocarbons, which are rich in virgin samples. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) were sequentially established to discriminate between recycled and virgin PE based on VOC markers. Our findings indicate that there are significant differences in VOCs between recycled and virgin PE, and HS-GC-MS in combination with multivariate statistical analysis can be a reliable tool for discrimination of recycled and virgin PE.